Qualitative methodology : a practical guide - Mills, Jane; Birks, Melanie (London Sage, 2014)
Fresh, insightful and clear, this exciting textbook provides an engaging introduction to the application of qualitative methodology in the real world. Expert researchers then trace the history and philosophical underpinnings of different methodologies, explore the specific demands each places upon the researcher and robustly set out relevant issues surrounding quality and rigor. Featured methodologies include action research, discourse analysis, ethnography, grounded theory, case studies and narrative inquiry. This practical book provides a helpful guide to the research process - it introduces the relevant methods of generating, collecting and analysing data for each discrete methodology and then looks at best practice for presenting findings. This enables new researchers to compare qualitative methods and to confidently select the approach most appropriate for their own research projects.
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Methodology; Qualitative research